PENGARUH EDUKASI PEMROGRAMAN JARAK JAUH BAHASA PYTHON PADA SIKAP EFIKASI KOTA BATAM - Jesica; Hendi Sama (P3M Institut Teknologi Pagar Alam, 2023)
In the era of information technology as it is today, everything can be learned, including learning programming languages. A novice programmer can self-learn by using specific websites that provide instructional materials, while also facing challenges related to where to code. Through this approach, beginners can gauge the extent of their knowledge in a particular language. The research aims to analyze the impact of programming language education websites on self-efficacy in Batam City. The researcher designed a website using the agile scrum method and conducted the analysis using quantitative research methods with random sampling techniques, collecting data from 384 respondents. The results obtained indicate that a higher level of self-efficacy corresponds to an increased understanding of programming. The importance of understanding programming in today's digital era not only aids beginners in developing their technical skills but also holds the potential to enhance their career opportunities in the continually evolving world of information technology industry.